(untitled) (Genius Repository, 2023)
This article examines the development of the national periodical press in Central Asia. The press was, according to the educators, the most important instrument of ideological influence on the consciousness of the general public. The press reflected the intellectual movement, and was also a kind of tribune that brought to the masses the reformist ideas of renewing society.